3(n-7)=-30
3n-21= -30
3n = -9
n= -3
Answer:
(x, g(x)) = {(-2, -2), (0, 0), (2, 2), (4, -3), (6, -3)}
Step-by-step explanation:
The first three values of x in the table are all less than or equal to 2, so the first part of the function definition applies. The y-value is equal to the x-value. The ordered pairs are ...
(-2, -2), (0, 0), (2, 2)
The last two values of x in the table are more than 2, so the last part of the function definition applies. For those values of x, the y-value is -3. The ordered pairs are ...
(4, -3), (6, -3)
Answer:
A 16. B 20). C 40 ... 40' 60'| 80. 20 20 20. 2 7 14a. 40 140|| 280'|. BX Hours. Earnings ($).
Step-by-step explanation:
Answer:
Step-by-step explanation:
√x^72 = √(x^36)^2 = x^36